2005
DOI: 10.1073/pnas.0405957102
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac stem cells delivered intravascularly traverse the vessel barrier, regenerate infarcted myocardium, and improve cardiac function

Abstract: The ability of cardiac stem cells (CSCs) to promote myocardial repair under clinically relevant conditions (i.e., when delivered intravascularly after reperfusion) is unknown. Thus, rats were subjected to a 90-min coronary occlusion; at 4 h after reperfusion, CSCs were delivered to the coronary arteries via a catheter positioned into the aortic root. Echocardiographic analysis showed that injection of CSCs attenuated the increase in left ventricular (LV) end-diastolic dimensions and impairment in LV systolic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
317
3
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 434 publications
(332 citation statements)
references
References 29 publications
5
317
3
7
Order By: Relevance
“…Serial echocardiograms were obtained at 5 time points: baseline (3 days before coronary artery occlusion), 30 days after MI (before the first treatment), 35 days after the first treatment (before the second treatment), 35 days after the second treatment (before the third treatment), and 35 days after the third treatment (before euthanasia; Figure 1). The echocardiographic studies were performed as described3, 7, 8, 9, 10 using a Vevo 2100 Imaging System equipped with a 20‐MHz transducer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Serial echocardiograms were obtained at 5 time points: baseline (3 days before coronary artery occlusion), 30 days after MI (before the first treatment), 35 days after the first treatment (before the second treatment), 35 days after the second treatment (before the third treatment), and 35 days after the third treatment (before euthanasia; Figure 1). The echocardiographic studies were performed as described3, 7, 8, 9, 10 using a Vevo 2100 Imaging System equipped with a 20‐MHz transducer.…”
Section: Methodsmentioning
confidence: 99%
“…The hemodynamic studies were conducted 35 days after the third treatment, just before euthanasia (Figure 1). The protocol has been described previously 3, 7, 8, 9, 10…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that c-Kit + cardiac stem cells isolated from the adult rat heart home to infarcted areas when delivered via the aortic root during a reperfusion protocol, improving LVEF 5 weeks post-MI (LVEF ≈ 48% treated vs LVEF ≈ 40% control [P <.05] compared to baseline LVEF ≈ 75%), and regenerate muscle and vessels in the absence of cell fusion as demonstrated by the presence of at most two copies of chromosome 12 (detected by fluorescence in situ hybridization) in newly formed green fluorescent protein (GFP)-positive cardiomyocytes. 10 This study represents an important step toward clinically relevant application of cardiac stem cells.…”
Section: C-kit + Cardiac Stem Cellsmentioning
confidence: 98%
“…Elle permettrait notamment de comprendre l'observation d'un nombre restreint de cardiomyocytes en mitose et la présence de cellules progénitrices vasculaires dans le tissu cardiaque, dont l'origine, médullaire ou endogène cardiaque, est très débattue. Enfin, ces cellules souches cardiaques pourraient servir de base à des thérapies cellulaires développées pour le traitement des pathologies cardiaques [11].…”
Section: Progéniteurs Endothéliaux Circulantsunclassified